To a question of introduction of criminal liability of legal entities. (Journal of actual problems of jurisprudence, 2016)
The article discusses issues related to the introduction of criminal liability of legal persons. The authors examined the nature of the legal entity, revealed signs of a legal entity, the analysis of property liability of legal persons. Through the definition of the legal nature of the legal entity, the ratio of civil liability and criminal liability, functions and purposes of these types of liability conclusions inexpedient introducing criminal liability of legal persons.
Keywords: legal entity; legal liability; civil pravovoya responsibility; criminal responsibility; function and purpose of criminal liability; property damage